Capturing the Stories behind the Numbers: The Auckland Regional Community Stroke Study (ARCOS IV), a Qualitative Study. Issue 1 (January 2014) - Rutherford, Sandy J.; Theadom, Alice; Jones, Amy; Hocking, Clare; Feigin, Valery; Krishnamurthi, Rita; Kent, Bruce; Barker-Collo, Suzanne; McPherson, Kathryn M.
Background: Qualitative data can add value and understanding to more traditional epidemiological studies. This study was designed to complement the quantitative data from the incidence study the Auckland Regional Community Stroke Study or ARCOS-IV by using qualitative methods to uncover the richer detail of life as a stroke survivor, thereby extending our understanding of the impact of stroke. Aims: The aims of the study were to identify how the experience of recovery and adaptation changes over time after stroke; and to elicit the strategies people with stroke and their whānau/family use and find helpful in living life after stroke. The aim of this paper is to describe the methodology and also the challenges and advantages of embedding qualitative research into a large epidemiological study. Methods: Longitudinal study utilizing a Qualitative Description design in a subset of those taking part in the incidence study. Participants will be interviewed at 6, 12, 24, and 36 months after stroke. Semistructured interviews will explore three key areas: (1 ) issues of importance to people following a stroke and their whānau/family; (2 ) the perceived impact on people's sense of recovery, adaptation, and hopes; and (3 ) key strategies that people with stroke and their whānau/family use and find most helpful in living life after stroke. Thematic analysis will be conducted using iterative constant comparative methods. Conclusions: This methodology paper demonstrates the application of mixed methods in epidemiology. It also considers some of the practical and methodological issues that have emerged and may provide a useful framework for other qualitative projects in population-based studies.